Moderating influence of emotional intelligence in the relationship between domain-based self-efficacy and task performance: A study of employee in Nigerian banking industry - Adekiya, Adewale; Aliyu, Mukhtar Shehu; Bello, Garba Bala; Kofar-Mata, Bala Ado (Ekonomia Międzynarodowa, 2021)
Given the lowering of trade barriers among nations, the internet revolution, and a resultant increase in the bargaining power of consumers, coupled with the economic impact of COVID-19 pandemic, firms are increasingly forced to make use of a high performing workforce. It is to raise the quality of their products and/or services as global competition for the consumer’s money severely punishes inefficiencies. As a result of this, it has become imperative for organizational researchers to determine the important antecedents of employee task performance. Hence, the purpose of this study is to examine the relationship between the domain-based self-efficacy and employee task performance. Drawing on the Social Cognitive Theory, we propose that there is a relationship between these two variables, and that the relationship is moderated by emotional intelligence, with the view of shedding light on the inconsistent nature of the results from previous studies. Through the descriptive survey research design, the multi-stage sampling technique was applied in eliciting data from a total of 342 employees of the Nigerian banking industry who are employed in the customer services sector. From the simple moderation analysis conducted after utilizing the Process macro, results indicate that there is a positive and significant relationship between domain-based self-efficacy and task performance. However, emotional intelligence moderates this relationship in such a way that the positive relationship between self-efficacy and task performance was weaker among subjects who reported a higher level of emotional intelligence. In the light of these findings, it was recommended for managers particularly in the banking industry to set up intervention strategies that have the potentials of promoting a desirable level of domain-based self-efficacy among their employees while also ensuring that an optimal mix of emotional intelligence both within and across components is promoted with the view of achieving a desirable moderating impact of this relationship.